(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Vincristine is an anticancer agent administered to all children with acute lymphoblastic leukemia (ALL), and peripheral neuropathy is the major dose-limiting toxicity of this therapy. As cure rates of childhood ALL exceeds 80%, therefore treatment-related toxicities need to be reduced. Thus, the aim of this study was to determine the prevalence and risk factors of vincristine-induced peripheral neuropathy (VIPN) in children with ALL undergoing induction chemotherapy. Methods: A case-control study was conducted from September 2017 to August 2018 in the Department of Paediatric Haematology and Oncology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Eighty newly diagnosed ALL and 35 acute myeloid leukemia (AML) cases aged 5 to 17 years with no pre-existing neurological abnormality were recruited. To assess the peripheral neuropathy, we used pediatric-modified total neuropathy score and National Cancer Institute- Common Terminology Criteria for Adverse Events (NCI-CTCAE), version-04 grade. Results: Among ALL patients, 29.2% developed peripheral neuropathy compared to 10% in AML control group (P=0.04). Higher proportion (57.1%) of peripheral neuropathy was found in age below 10 years (P<0.001). There was no significant association of peripheral neuropathy with sex and body mass index of the patients. Conclusion: Almost 3 in 10 patients developed VIPN during the induction therapy which is significantly higher in age below 10 years compared to ≥ 10 years.